Answer:
x = 3 and y = -1
Explanation:
To solve a system of equations, use graphing, substitution, or elimination. Here we use substitution. In substitution, solve one equation for a variable. Then substitute the equation into another equation. this creates an equation in one variable. Then solve for the variable.
Solve 2x - 3y = 9 for x.
2x - 3y = 9
2x = 9 + 3y
x = 9/2 + 3/2y
Substitute this equation into 3x + 5y = 4.
3(9/2+3/2y) + 5y = 4
27/2 + 9/2 y + 5y = 4
Clear the fractions by multiplying everything by 2.
27 + 9y + 10y = 8
27 + 19y = 8
19y = -19
y = -1
Substitute y = -1 into 2x - 3y = 9 to solve for x.
2x -3(-1) = 9
2x + 3 = 9
2x = 6
x = 3